Biodistribution of extracellular vesicles following administration into animals: A systematic review. Issue 8 (24th June 2021) - Kang, Matthew; Jordan, Vanessa; Blenkiron, Cherie; Chamley, Lawrence W.
Abstract: In recent years, attention has turned to examining the biodistribution of EVs in recipient animals to bridge between knowledge of EV function in vitro and in vivo. We undertook a systematic review of the literature to summarize the biodistribution of EVs following administration into animals. There were time‐dependent changes in the biodistribution of small‐EVs which were most abundant in the liver. Detection peaked in the liver and kidney in the first hour after administration, while distribution to the lungs and spleen peaked between 2–12 h. Large‐EVs were most abundant in the lungs with localization peaking in the first hour following administration and decreased between 2–12 h. In contrast, large‐EV localization to the liver increased as the levels in the lungs decreased. There was moderate to low localization of large‐EVs to the kidneys while localization to the spleen was typically low. Regardless of the origin or size of the EVs or the recipient species into which the EVs were administered, the biodistribution of the EVs was largely to the liver, lungs, kidneys, and spleen. There was extreme variability in the methodology between studies and we recommend that guidelines should be developed to promote standardization where possible of future EV biodistribution studies.